Initial Steps of Amyloidogenic Peptide Assembly Revealed by Cold‐Ion Spectroscopy. (7th December 2017) - Ujma, Jakub; Kopysov, Vladimir; Nagornova, Natalia S.; Migas, Lukasz G.; Lizio, Maria Giovanna; Blanch, Ewan W.; MacPhee, Cait; Boyarkin, Oleg V.; Barran, Perdita E.
Abstract: The early stages of fibril formation are difficult to capture in solution. We use cold‐ion spectroscopy to examine an 11‐residue peptide derived from the protein transthyretin and clusters of this fibre‐forming peptide containing up to five units in the gas phase. For each oligomer, the UV spectra exhibit distinct changes in the electronic environment of aromatic residues in this peptide compared to that of the monomer and in the bulk solution. The UV spectra of the tetra‐ and pentamer are superimposable but differ significantly from the spectra of the monomer and trimer. Such a spectral evolution suggests that a common structural motif is formed as early as the tetramer. The presence of this stable motif is further supported by the low conformational heterogeneity of the tetra‐ and pentamer, revealed from their IR spectra. From comparison of the IR‐spectra in the gas and condensed phases, we propose putative assignments for the dominant motif in the oligomers.